Antineuron specific enolase staining reactions in sarcomas and carcinomas: its lack of neuroendocrine specificity. Issue 11 (November 1986) - Leader, M; Collins, M; Patel, J; Henry, K
Abstract : A commercially available polyclonal antiserum (Dakopatts) raised against bovine neuron specific enolase (NSE) was reacted with 197 sarcomas, 32 carcinomas, 11 carcinoid tumours and 20 malignant melanomas to assess its specificity for neuroendocrine tumours. All the tumours had been fixed in formalin and embedded in paraffin. Positive tumour cells were found in two of 11 squamous cell carcinomas, one of 11 adenocarcinomas, 10 of 10 oat cell carcinomas, 11 of 11 carcinoid tumours, 16 of 20 malignant melanomas, four of seven clear cell sarcomas, nine of 25 leiomyosarcomas, four of 22 rhabdomyosarcomas, one of seven angiosarcomas and one of 20 synovial sarcomas.